IDENTIFIKASI RISIKO PRODUKSI DAN PEMASARAN ALAT TEKNOLOGI LTI PADA CV JOGLO NUSANTARA - Rahman Dwi Irvanto; Ifan Rizky Kurniyanto; Mokh Rum (Jurnal Agribisnis Indonesia, 2024)
CV. Joglo Nusantara is a business in the agriculture sector that produces agricultural technology tools. One of the products made by CV Joglo is LTI (Light Trap Insect). LTI functions as an alternative deterrent to pest attacks on rice fields. Nevertheless, CV Joglo has a risk in production operations because the machine was damaged and needs to wait for the machine to be repaired. In addition, there is a marketing risk due to promotional obstacles in online media through the pre-order system. This research aimed to determine production and marketing risks and provide risk mitigation for the highest risks in CV. Joglo Nusantara. This research used fishbone diagram analysis tools and FMEA (Failure Model and Effecct Analysis). The results showed four production risk indicators: human resource risk, raw materials, equipment/machinery, and process. The results of marketing risk are two indicators in the form of market risk and promotion. Risk mitigation activities in CV. Joglo Nusantara on priority risks, namely production risks, by checking LTI equipment production machines, selecting raw materials that get quality standards, improving communication with fellow workers, and mitigating marketing risks by guiding CV owners on how to promote LTI technology tools by implementing a pre-order system to online media such as Instagram, Facebook, and WhatsApp by posting photos and videos of LTI.